The Role of Brand Awareness in Mediating the Influence of Promotion Through Social media On Purchase Intention : Study on Coffee Shops “Sekopi” in Denpasar City - Ni Wayan Arum Maha Dharmeitreya; Ni Wayan Sri Suprapti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The high consumption of coffee and the phenomenon of changes in people's lifestyles support coffee shop business opportunities.